(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Abstract Vehicular Ad hoc Network (VANET) is a specialized Ad hoc Network, which provides safety and comfort for passengers [1]. Due to the specific characteristic of VANET like high mobility and large scale node population [1], providing Quality of Service (QoS) in this type of wireless network is a challenging issue. As a result, we combine Mobile IP and VANET to improve QoS in terms of packet loss and throughput for traffic safety and entertainment applications. Comparative performance evaluation is done in terms of QOS parameters to show the network performance using different traffic types and by varying speed of the vehicles under urban scenario.